Transactional Culture and the Reproduction of Patronage: Reading the Dawn Attack as a Socio-Political Practice in Lamongan, Indonesia - Diva Mahkota Putri; Alessandra Decataldo; Kenechukwu Emmanuel Nnamani (Journal of Religion, Local Politics, and Law, 2025)
The phenomenon of dawn attacks in the 2024 Regional Head Election (Pilkada) in Lamongan Regency represents a tangible form of transactional political culture that has been institutionalized in local democratic practices. This article aims to examine the dawn attack not just as a violation of election laws but as a social practice that reflects the reproduction of patronage between the political elite and the voting community. This study employs a qualitative approach with a case study design, collecting data through in-depth interviews, participatory observations, and document analysis from election organizers, winning teams, and Lamongan residents. The results indicate that dawn attacks are facilitated through robust social networks, where patron-client relationships play a crucial role in exchanging economic resources for political support. The practice is rooted in reciprocity and social norms that justify giving money as a form of political solidarity. As a result, the dawn attack not only perpetuates power inequality but also reduces the meaning of democratic participation to pragmatic economic relations. These findings confirm that local democracy in Lamongan is still colored by a patronage culture that continues to be reproduced through social, symbolic, and structural mechanisms